Toward Understanding the Alginate Catabolism in Microbulbifer sp. ALW1 by Proteomics Profiling - Li, Zhipeng; Huang, Xiaoyi; Guo, Yuxi; Zhang, Chenghao; Yang, Liang; Du, Xiping; Ni, Hui; Wang, Xuchu; Zhu, Yanbing (Frontiers in Bioengineering and Biotechnology, 2022)
The bacterial strain of Microbulbifer sp. ALW1 has demonstrated visible ability of degrading the celwall of Laminaria japonica, and biochemical characterization has been performed on some individual enzymes to elucidate its genetic basis. However, it still remains elusive how strain ALW1 successfully breaks down the major cell wall component alginate polysaccharide and colonizes on its marine host. In this study, a mass spectrometry-based quantitative analysis of the extracellular and intracellular proteomes was introduced to elucidate the alginate degradation pathway in ALW1 strain. Mass spectrometry and biochemical assays indicated that strain ALW1 could effectively degrade alginate polysaccharide into disaccharides and trisaccharides within 12 h. Proteome analysis identified 156 and 1047 proteins exclusively localized in extracellular and intracellular compartments, respectively, with 1086 protein identities of dual localization. Functional annotation of the identified proteins suggested the involvement of diverse catalytic enzymes and non-catalytic molecules for the cleavage and metabolism of alginate polysaccharide. A simplified pathway was constructed to demonstrate the extracellular digestion, active transport, and intracellular conversion of alginate polysaccharide and its fragmented oligosaccharides, casting a picture of genetic loci controlling alginate catabolism by ALW1 strain. This study aims to provide a guide for utilization and genetic manipulation of the bacterial strain ALW1 for efficient alginate oligosaccharides production by fermentation.